Reform of the Policy on Public Debt Limits in IMF-Supported Programs. (Policy Papers; Policy Paper, 2020)
This paper evaluates the IMF's policy on the use of quantitative limits on public debt in IMF-supported programs (the 'debt limits policy') and proposes a number of modifications. The review is taking place at a time when many countries are experiencing heightened debt vulnerabilities or actual debt distress, aggravated by the COVID-19 shock, and occurring against the backdrop of a changing credit landscape in which concessional finance is scarcer relative to countries' investment needs.